Underwater archeology research in Peninsular Malaysia (1902-2015) - Zainuddin Baco; Stephen Chia (Ikatan Ahli Arkeologi Malaysia, 2020)
Underwater archaeological research in Peninsular Malaysia has spanned more than a century, a period that is supposed to show that the field has been solid in terms of its research, technology and research findings. However, the area of underwater archaeological research has not grown properly as it is often dominated by commercial salvage experts and treasure hunter. It is undeniable that Malaysia is like any other country that has not been exposed to various issues and fundamental problems in developing this field. However, the alternative of using a commercial salvage company in developing and conducting research using the concept of concession distribution should be the last choice. Thus, this article will highlight the history of archaeological research in Peninsular Malaysia through three distinct phases, namely the pre-independence phase (up to 1980), the JMA phase (1980- 2005) and the JWN phase (2006-2019). Each of these phases is in accordance with stakeholder management methods and policies.